New genera, new species and redescriptions of Australian jumping spiders (Araneae: Salticidae) - Richardson, Barry J. (Zootaxa, 2016)
A number of Australian species have been placed in the wrong, often non-Australian, genera. Some of these problems have been corrected here, by transfer or establishment of new genera. Several new species discovered during the course of the work are also described. Marptusa jovialis L. Koch, 1879 and Marptusa bracteata L. Koch, 1879 are transferred to Apricia gen. nov. Apricia longipalpis sp. nov. is also described from Australia. The study of the Australian species presently included in Trite Simon 1885 showed that this genus does not occur in mainland Australia. Hence, Marptusa vulpecula Thorell, 1881 is transferred to Capeyorkia gen. nov., while Marptusa longula Thorell, 1881 is transferred to Evarcha Simon, 1902. The only previously described ‘Australian’ species to remain in Trite is Trite concinna Rainbow, 1920, from Lord Howe Island and Norfolk Island in the Pacific, while Trite grayi sp. nov., also from Lord Howe Island, is described here. Trite concinna Rainbow 1920 is redescribed. Most specimens previous listed as this species from Lord Howe Island (including most of the syntype series) belong in Ancepitilobus howensis gen. nov. et sp. nov. Clynotis severus (L. Koch, 1879) is the solitary species that remains in Clynotis Simon, 1901, with the remainder of the mainland species being transferred to Pungalina Richardson, 2013: P. albobarbata (L. Koch, 1879) comb. nov., P. semiatra (L. Koch, 1879) comb. nov. and P. semiferruginea (L. Koch, 1879) comb. nov. Pungalina plurilineata sp. nov. and Pungalina waldockae sp. nov. are also described from Australia. Clynotis gratiosa from Lord Howe Island is formally transferred to Tara Peckham & Peckham, 1886, as suggested previously. Tara gratiosa (Rainbow, 1920) is redescribed. Finally, three names, Gangus longulus Simon, 1902, Trite ornata Rainbow, 1915 and Plexippus albopilosus Keyserling, 1883, are considered species inquirendae, due to the state or loss of type material.